2014
DOI: 10.1111/jop.12298
|View full text |Cite
|
Sign up to set email alerts
|

TLR2,TLR4 and CD86 gene polymorphisms in recurrent aphthous stomatitis

Abstract: This is the first study to investigate the association of TLR and CD86 with RAS. We found a significant association between TLR4 rs10759931 polymorphism and RAS. Confirmatory studies in other populations and functional investigations are needed to determine the role of TLR4 in RAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
0
15
0
3
Order By: Relevance
“…These authors also identified a correlation between the serotonin transcriptase encoding gene polymorphisms and recurrent aphthous ulceration, implicating the potential role of stress and psychogenic stimuli in ulcer development 35. Karasneh and colleagues recently demonstrated the likely relationship between toll‐like receptor 4 rs10759931 polymorphism and recurrent aphthous ulceration 36. They note that future studies would be valuable relative to potentially targeting the toll‐like receptor as a treatment strategy for the lesion 36.…”
Section: Phenotype Incidence and Pathobiology Of Mtor Inhibitor–assmentioning
confidence: 99%
See 2 more Smart Citations
“…These authors also identified a correlation between the serotonin transcriptase encoding gene polymorphisms and recurrent aphthous ulceration, implicating the potential role of stress and psychogenic stimuli in ulcer development 35. Karasneh and colleagues recently demonstrated the likely relationship between toll‐like receptor 4 rs10759931 polymorphism and recurrent aphthous ulceration 36. They note that future studies would be valuable relative to potentially targeting the toll‐like receptor as a treatment strategy for the lesion 36.…”
Section: Phenotype Incidence and Pathobiology Of Mtor Inhibitor–assmentioning
confidence: 99%
“…Until further research determines the molecular basis of mIAS, it is thus biologically plausible to conceptualize a pathobiologic model of mIAS in relation to the multifactorial mechanistic basis and clinical profile of recurrent aphthous ulceration as defined in the literature (Table 2) 7, 9, 10, 30, 31, 32, 33, 34, 35, 36, 37. Possible risk factors for recurrent aphthous ulceration have classically included anxiety and stress, hormonal alteration, and/or nutritional deficiency.…”
Section: Phenotype Incidence and Pathobiology Of Mtor Inhibitor–assmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to my best knowledge by the time of writing this manuscript (08/11/2019), no articles were found in Pubmed-NCBI data base when searching for key words as 'TLR4 SNP Iraq'. Although, when searched for 'TLR4 polymorphism Iraq' only one article was published that was about TLR4 Asp299Gly SNP (rs4986790) and the samples were taken from Jordanian populations but one of its authors is from Iraq [15] . Similarly, no data were found for TLR4 SNP in Syria as a country of having Kurdish populations.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6][7] Predispozan faktörlerin aksine sigara ve dumansız tütün kullanımının RAS oluşumunu engellediği düşünülmektedir.…”
unclassified